2022
DOI: 10.3389/fmolb.2022.838654
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene Signature Associated With “E2F Target” Pathway for Predicting the Prognosis of Prostate Cancer

Abstract: Background: The effect of the adenoviral early region 2 binding factors (E2Fs) target pathway on prostate cancer is not clear. It is necessary to establish an E2F target-related gene signature to predict prognosis and facilitate clinical decision-making.Methods: An E2F target-related gene signature was established by univariate and LASSO Cox regression analyses, and its predictive ability was verified in multiple cohorts. Moreover, the enrichment pathway, immune microenvironment, and drug sensitivity of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…NEPC has been defined as a disease that is highly transcriptionally active regulating proteins involved in DNA replication (for example DNA polymerase, thymidine kinase, dihydrofolate reductase and cdc6), and chromosomal regulation ( 60 ), whereas prostate cancer AdCa that expresses AR and without neuroendocrine features is highly metabolically ( 61 ) regulated. Furthermore, it has been shown that mRNA from transcription factors have increased average decay rates compared with other mRNA transcripts and are enriched for “fast-decaying” mRNA transcripts with half-lives <2 hours ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…NEPC has been defined as a disease that is highly transcriptionally active regulating proteins involved in DNA replication (for example DNA polymerase, thymidine kinase, dihydrofolate reductase and cdc6), and chromosomal regulation ( 60 ), whereas prostate cancer AdCa that expresses AR and without neuroendocrine features is highly metabolically ( 61 ) regulated. Furthermore, it has been shown that mRNA from transcription factors have increased average decay rates compared with other mRNA transcripts and are enriched for “fast-decaying” mRNA transcripts with half-lives <2 hours ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several E2F target genes are tightly connected, which may help predict tumor prognosis. An E2F target gene signature, formed by MDX3, PLK1, EPHA10, and KIF4A, exhibited a stronger predictive power than existing signatures in prostate cancer ( Xia et al, 2022 ). Hu et al (2022) established an E2F target gene signature composed of five genes (HN1, KIF4A, CDCA3, CDCA8, and SSRP1) and found it is significantly related to the prognosis of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…E2Fs detach from the E2F-RB1 complex and promote cell cycle-dependent gene transcription when RB1 is altered or phosphorylated ( van den Heuvel and Dyson, 2008 ; Zheng et al, 2023 ). Upregulation of E2F target genes is correlated with poor outcomes of neuroblastoma, breast cancer, colorectal cancer, ovarian cancer, and prostate cancer ( Molenaar et al, 2012 ; Dahl et al, 2019 ; Oshi et al, 2021 ; Xia et al, 2022 ; Xu et al, 2022 ). Moreover, the E2F score serves as a predictive biomarker of response to neoadjuvant chemotherapy in estrogen receptor (ER)-positive/human epidermal growth factor receptor 2 (HER2)-negative breast cancer patients ( Oshi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…E2F1 and E2F2 are upregulated in several cancer types, including prostate cancer (PCa) [7,8], in which overexpression of these E2Fs correlates with poor clinical outcome [9,10]. In this regard, it has been suggested that cancer cells rely on E2F function to tolerate the exceptionally high levels of basal or drug-induced DNA replication stress that cancer cells endure [11,12].…”
Section: Introductionmentioning
confidence: 99%